How Successful is Naturalism? - Gasser, Georg (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2007)
Naturalism is the reigning creed in analytic philosophy. Naturalists claim that natural science provides a complete account of all forms of existence. According to the naturalistic credo there are no aspects of human existence which transcend methods and explanations of science. Our concepts of the self, the mind, subjectivity, human freedom or responsibility is to be defined in terms of established sciences. The aim of the present volume is to draw the balance of naturalism's success so far. Unlike other volumes it does not contain a collection of papers which unanimously reject naturalism. Naturalists and anti-naturalists alike unfold their positions discussing the success or failure of naturalistic approaches. "How successful is naturalism? shows where the lines of agreement and disagreement between naturalists and their critics are to be located in contemporary philosophical discussion.